2005
DOI: 10.3138/jvme.32.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring within the Veterinary Medical Profession: Veterinarians’ Experiences as Protégés in Mentoring Relationships

Abstract: Veterinary medicine professionals have recognized the importance of enhancing mentoring of students, as recruitment and retention of students have become prominent concerns. The purpose of the present study was to examine the form and degree of mentoring experienced by practicing veterinarians, as well as to seek to understand the factors that influence effective mentoring relationships. Data concerning their own experiences with mentoring relationships were gathered from practicing veterinarians. Results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Employees' perceived career opportunities and the availability of career mentoring has been shown to predict employee turnover in non-animal related services ( 15 , 16 ). Students and veterinarians have also recognized the importance of mentorship in the veterinary profession ( 17 , 18 ). However, in a New Zealand study of recent veterinary graduates, almost half of the respondents reported they did not regularly meet with their supervisor to discuss their work or have a clear plan to develop their skills or experience.…”
Section: Discussionmentioning
confidence: 99%
“…Employees' perceived career opportunities and the availability of career mentoring has been shown to predict employee turnover in non-animal related services ( 15 , 16 ). Students and veterinarians have also recognized the importance of mentorship in the veterinary profession ( 17 , 18 ). However, in a New Zealand study of recent veterinary graduates, almost half of the respondents reported they did not regularly meet with their supervisor to discuss their work or have a clear plan to develop their skills or experience.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in human medicine, where recent graduates enter structured specialized training programs, newly graduated veterinarians often enter general practice without additional formal training (Mastenbroek et al., 2015). Most veterinary graduates seek to join a practice where some degree of mentorship is provided (Barbur et al., 2011; Mastenbroek et al., 2015; Niehoff et al., 2005). It takes time to hone the skills acquired during the veterinary curriculum and new graduates need experience and time to grow their confidence (Routly et al., 2002).…”
Section: Benefits Of Mentoring In Veterinary Medicinementioning
confidence: 99%
“…Mentoring efforts are multi‐faceted (i.e., a “mosaic model”) and may evolve over one's career (Elce, 2021). Some veterinarians report having received pre‐veterinary mentorship during undergraduate training or even high school; others report that most mentoring relationships started during their early post‐DVM career (Niehoff et al., 2005). Ideally, mentorship should start at the beginning of the veterinary curriculum, and can be carried throughout a lifetime (Elce, 2021; Niehoff et al., 2005).…”
Section: Mentoring Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness of the relationship among the veterinary profession has been raised [17]. Bailey [18] could say that the students are clients in professionalclient relationship (Table 1) because in such circumstances they receive signals; a different set of expectations, responsibilities and a respect typical of their own profession.…”
Section: Nonverbal Communication Betweenmentioning
confidence: 99%